PENGARUH KONFLIK PERAN DAN AMBIGUITAS PERAN TERHADAP KOMITMEN INDEPENDENSI AUDITOR INTERNAL - Lusius Kharismawan Sindudisastra; Rustiana Rustiana (Modus, 2014)
This study was conducted to assess and identify the infuence of role confict and role ambiguity of the internal auditor independence commitment to work in rural banks Yogyakarta Special Region. Determination of the respondents was conducted by sampling purporsive ie sampling technique based on a certain criteria. The number of questionnaires distributed is as much as 25 questionnaires. This study uses a simple linear regression. Results of analysis in this study indicate that role confict and ambiguity each negatively afect the independence of the internal auditor commitment.Keywords: role confict, role ambiguity, internal auditor independency.